The Relation between Corporate Social Responsibility and Bank Reputation: A Review and Roadmap - Lorena, Antonio (European Journal of Economics and Business Studies, 2018)
Over the past decades, scholars have paid greater attention to relation between Corporate Social Responsibility (CSR) and corporate reputation. However, despite a growing interest in this area, such linkages have remained relatively unexplored in the banking industry and the precise relationship is not clear. Moving from these considerations, this study proposes a systematic review of peer-reviewed scientific literature aiming to: 1) list, 2) classify and 3) compare existing studies. The review was carried out using the following databases: ISI Web, Google Scholar, and SSRN. I investigate a number of publishing academic works, summarizing main approaches, results and insights. I also provide a roadmap for future study and offer research questions about critical areas of this stream of research. The paper contributes to the ongoing international debates, and the preliminary results are encouraging.
Keywords: Corporate Social Responsibility, reputation, bank1.